Prevalence and Management of Ocular Trauma in Two Municipalities of Nepal - Shrestha, Mohan Krishna; Basnet, Pushpa Babu; Poudel, Manish; Sharma, Shaifali; Gurung, Reeta (Nepalese Journal of Ophthalmology, 2026)
Introduction: Female Community Health Volunteers (FCHVs) play a crucial role in promoting and preventing of eye health problems.Objective: To assess the prevalence of and management of corneal abrasions using ophthalmic antimicrobials by FCHVs in urban areas of Nepal.Methodology: This retrospective study reviews the data of ocular trauma between 2019 January and 2022 December of Nilkantha and Solududhkunda Municipalities, Nepal. The FCHVs were trained to diagnose corneal abrasions and provide a 3-day course of antimicrobials and referred unresolved cases to Eye Centres for further management. Data were analysed with IBM SPSS v.20. Chi-square and Fisher’s exact tests were used. A 95% confidence interval was calculated, and significant variables were analysed through multiple logistic regression.Result: All together 1,949 ocular trauma cases utilised the community-based eye care services provided by FCHVs. The prevalence of corneal abrasion was 87.3% (1,701), with a higher prevalence in Nilkantha (70.3%; n=1,195) than Solududhkunda (29.7%; n=506). In corneal abrasion cases, the mean age ± SD of the participants were 38.9 ± 18.1, (39.4±18.2 in Nilkantha and 37.7±17.8 in Solududhkunda municipalities). The prevalence of corneal abrasion was 47.9 % (814) in male and 52.1% (887) in female. The recovery rate of corneal abrasion was 97.4% (95% CI: 96.6–98.1; p